Conceptual Thinking in Design Studios: Upon Music and form Relation - Dilara Onur; Betül Akgül (International Journal of Architectural Engineering Technology, 2017)
In today’s ever-changing and ever-growing world, new teaching and learning strategies are the focus of attention in order to develop creative thinking in design training. Previous applications of imaginative and formal methods are being evaluated to see their inadequacies, and new approaches are being discussed. Both imagination and form- based approaches are employed to develop creative thinking. Whereas imagination based approaches develop students’ creative thinking, form based ones let them have three dimensional thinking and develop their skills of form creation. In this regard, abstraction- based design studies, which depend upon imagination and concept, are often used to develop students’ form creation skills. Several abstract and concrete different disciplines are starting points in design studios, which enrich students’ imagination and help them develop thinking skills. Music was employed as a source of inspiration in form production using conceptual abstraction within this studio study which resulted from imaginative and formal interaction. In spring semester, 2014-2015 academic year, elective courses such as Creative Thinking and Seat Component, carried out by fellow teaching staff, appear in syllabus of Interior Architecture Department, KTU, and course content and outcomes of studio studies are to be scrutinized within this framework.